The Political Parties in the Practice of the Constitutional Court of the Republic of Bulgaria - Asenov, Simeon (Research Papers, 2011)
The study aims at motivating and analyzing the politological aspects in the practice of the Constitutional Court in regard with the control over the political parties’ constitutionality in Bulgaria. In the study the latter is laid and realized in the broader context of the interrelations between politics and law, interpreted through the prism of the conceptual generation and development of the constitutionalism and the political parties. The control of parties’ constitutionality is a new and weakly researched phenomenon within the Bulgarian democratic practice. Argumentatively is proven that except judicial it has and political dimensions which permits researching not only by the positions of the constitutional law but also by the political science.The politological analysis of jurisprudence in the Bulgarian practice shows the different proportion and mutual influence between the political elements and legal grounds in the assessment of constitutionality of parties. This analysis gives possibility for revelation of the degree to which the Constitutional Court neutralizes or amplifies with political aspects and dimensions its decision on juridical basis.